2014
DOI: 10.1111/jgh.12549
|View full text |Cite
|
Sign up to set email alerts
|

Markers of endothelial dysfunction in patients with non‐alcoholic fatty liver disease and coronary artery disease

Abstract: Background Non‐alcoholic fatty liver disease (NAFLD) has been associated with coronary artery disease (CAD) and cardiac‐related mortality. Aim To assess the association between endothelial dysfunction markers (Endocan, high mobility group box 1 [HMGB1], and anti‐endothelial cell antibodies [AECAs]) and the risk of CAD in NAFLD. Methods Ninety‐one patients scheduled for coronary angiography for chest pain were included. Of these, 77 had NAFLD (85% with documented CAD). NAFLD was diagnosed after exclusion of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…In some prospective cohort studies, it is showed that coronary heart disease is associated with NAFLD and this relationship is independent of classic risk factors for coronary heart disease. 22,23 This suggest epidemiological evidence for NAFLD promoting cardiovascular heart disease. In our study, one of the main aims was to find out if NAFLD is an independent risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…In some prospective cohort studies, it is showed that coronary heart disease is associated with NAFLD and this relationship is independent of classic risk factors for coronary heart disease. 22,23 This suggest epidemiological evidence for NAFLD promoting cardiovascular heart disease. In our study, one of the main aims was to find out if NAFLD is an independent risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…NAFLD patients exhibit increased levels of circulating ADMA, an association disappearing after correction for metabolic risk factors [50,52]. Other markers for endothelial dysfunction (e.g., endocan) were also increased in NAFLD [53].…”
Section: Endothelial Dysfunctionmentioning
confidence: 95%
“…Increased cIMT [30] Elevated serum elastase [43] elevated TGF-β [44] Arterial stiffening [28] Endothelium Endothelial dysfunction [27,28] Increased levels of ADMA [50,52] lower levels of HMGB1 [53] Endothelium disruption and repair [55] Reduced circulation EPCs [55] Redox status FGF21 ↑/FGF-resistance [124,125] CAD and NAFLD positively associated with FGF21 [126] SeP ↑ [127] Correlated with hsCRP and arterial stiffness [127] or cIMT [128] ANGPTL's ↑ [135] Associated with subclinical CVD [132][133][134] Paracrine cell signaling…”
Section: Observation Link With Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korean Journal of Gastroenterology 34,35 Portal hypertension affecting the systemic vascular resistance Metalloproteinase 38 Decreased elastic fiber and increased collagen in media of the large arteries increased arterial stiffness VEGF [39][40][41][42] Instability of atheroma 43,44 HMGB-1 45 Involving in Systemic inflammation and angiogenesis Dysfunction of endothelial cells ADMA 47 Increased arterial wall stiffness EMPs 48,49 Increased EMPs which are products of endothelial destruction Endothelial progenitor cell 48,49 Decreased endothelial progenitor cells which indicating endothelial repair function Inflammation and cytokine IL-1b 50 , IL-6 51,52 hs-CRP, TNF-a, CCL3, sICAM-1 51,53 Inflammation markers increased in NAFLD Homocysteine and inflammation Hyperhomocysteinemia [58][59][60] Oxidative stress, Decreased NO synthesis, Involving hepatic fibrosis Hepatokine and insulin resistance FetA 65 Increased inflammatory cytokine and insulin resistance and decreased adiponectin 65 Decreased vascular calcification by inhibiting TGF-β1signal pathway 65 FGF-21 [66][67][68] Increased level of FGF-21 for compensating insulin resistance in NAFLD SeP 69,70 Involving in Insulin resistance, hs-CRP, increased intimal thickness of carotid artery Lipid profiles TG, LDL, small dense LDL particles (LDL3, LDL4) 73 Increased in NAFLD, contributing to atherogenesis HDL 72 A defending factor of atherogenesis, but decrease in NAFLD. oxLDL 77 Contributing to oxidative stress in NASH and hepatic fibrosis Coagulation factors Factor 8, 9, 10, 12 78 Increased in NAFLD PAI-1 79,80 Increa...…”
Section: 김학수 조용균 비알코올 지방간 질환에서 심혈관 질환의 위험mentioning
confidence: 99%